Improvements in extraction yield by solid phase lipid extraction from liquid infant formula and human milk, and the fatty acid distribution in milk TAG analyzed by joint JOCS/AOCS official method Ch 3a-19 - Watanabe, Yomi; Hirokawa, Motoko; Furukawa, Arisa; Kawasaki, Lisa; Takumi, Hiroko; Masuyama, Araki (Frontiers in Nutrition, 2022)
The Röse-Gottlieb method is one of the most widely used methods for extracting lipids from milk samples. However, we found that lipid recovery from liquid infant formula and human breast milk was lower than expected. Better lipid recovery from these liquid matrices was obtained by solid phase extraction using silica gel; approximately 10% more could be recovered from liquid infant formula and ruminant milk, and 25% more from human breast milk. However, the method is not recommended for lipid extraction from dried whole milk powders.